Synthesis and Supramolecular Structure of 6,6’-Diethoxy-2,2’-[1,1’-(hexane-1,6-diyldioxy)bis(nitrilomethylidyne)]diphenol - Dong, Wen-Kui; Yang, Cheng-Juan; Liu, Sen-Hua; Wang, Li; Dong, Xiu-Yan (Asian Journal of Chemistry, 2013)
The compound, 6,6'-diethoxy-2,2'-[1,1'-(hexane-1,6-diyldioxy)bis(nitrilomethylidyne)]diphenol, was synthesized by the reaction of 3-ethoxysalicylaldehyde with 1,6-bis(aminooxy)hexane in ethanol. The molecule lies across a crystallographic inversion centre (symmetry code: -x, -y, -z) and adopts an E configuration with respect to the azomethine C=N bond. Within the molecule, the two benzene rings are parallel to each other and with the distance of 3.976(4) Å. Intramolecular O-H···N hydrogen bonds are formed between the hydroxyl groups and the oxime nitrogen atoms. The distances between the hydroxyl groups and the oxime nitrogen atoms d(O2···N1) = 2.626(3) Å. Intermolecular C-H···O hydrogen bonds link the title molecules into an infinite 3D supramolecular network structure.